(untitled) (CIPEEX, 2025)
This article is the result of research conducted on the impacts caused by the intensive use of pesticides in agriculture in Goiás, and aims to provide an analysis of the impacts of agrochemical use in the municipalities of the health regions of Northeastern Goiás, highlighting the main challenges faced by the local population. This is an exploratory and descriptive research of bibliographic analysis and secondary data on diseases related to pesticide use, with a quali-quantitative approach. Thus, data collection was carried out by surveying information from database systems, such as the Digital Information Systems of the Mauro Borges Institute and DataSUS. The analysis covers the period from 2010 to 2023 and has as its primary focus the health regions Northeast I and II in Goiás. Furthermore, the research revealed that there was an intensification of pesticide use in the state, reflected by the increase in cultivated areas and the quantities produced of soybeans, corn, and sugarcane, which has profound implications for public health. Therefore, the implementation of effective monitoring, education for rural workers, and reviewing pesticide policies is fundamental to ensure sustainable and safe agriculture in Goiás and Brazil.